THE IMPACT OF EMPLOYER BRANDING ON ORGANIZATIONAL PERFORMANCE: A COMPREHENSIVE ANALYSIS - Gurgu, Elena; Kuleto, Valentin (Annals of Spiru Haret University. Economic Series, 2023)
This article investigates the relationship between employer branding and organisational performance, identifying the underlying mechanisms contributing to enhanced performance. Next, we analyse various aspects of employer branding, including its influence on talent attraction, employee engagement, retention, and overall productivity. Finally, we provide insights on how organisations can strengthen their employer brand to optimise performance. In the competitive labour market, employer branding plays a crucial role in an organisation's ability to attract and retain top talent, directly influencing organisational performance. This article examines the relationship between employer branding and organisational performance by exploring its effects on talent attraction, employee engagement, retention, and overall productivity. It also offers insights on strengthening an organisation's employer brand to optimise performance. Employer branding, an organisation's reputation as an employer, can provide a competitive advantage by creating a motivated, engaged, and productive workforce. A strong employer brand attracts high-quality candidates, reducing recruitment time and cost and ensuring a diverse and talented candidate pool. Organisational culture, work environment, compensation and benefits, growth opportunities, and corporate social responsibility contribute to developing a strong employer brand. Effective employer brand communication across multiple channels, such as corporate websites, social media, and job advertisements, is essential to attract top talent. Employer branding events and employee advocacy can further strengthen the brand. Assessing the employer brand's strength can help organisations identify areas of improvement and gauge their attractiveness in the job market. Employee engagement and satisfaction are closely linked to an organisation's employer brand. Factors such as leadership, job design, recognition and rewards, work environment, and opportunities for growth and development contribute to employee engagement and satisfaction. Assessing employee engagement and satisfaction can provide valuable insights into their perceptions of the organisation and commitment to its goals. Engaged and satisfied employees exhibit higher performance, productivity, and innovation levels, leading to improved organisational outcomes.